Biomechanics of artificial pedicle fixation in a 3D-printed prosthesis after total en bloc spondylectomy: a finite element analysis - Xiaodong Wang; Hanpeng Xu; Ye Han; Jincheng Wu; Yang Song; Yuanyuan Jiang; Jianzhong Wang; Jun Miao (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background This study compared the biomechanics of artificial pedicle fixation in spine reconstruction with a 3-dimensional (3D)-printed prosthesis after total en bloc spondylectomy (TES) by finite element analysis. Methods A thoracolumbar (T10–L2) finite element model was developed and validated. Two models of T12 TES were established in combination with different fixation methods: Model A consisted of long-segment posterior fixation (T10/11, L1/2) + 3D-printed prosthesis; and Model B consisted of Model A + two artificial pedicle fixation screws. The models were evaluated with an applied of 7.5 N·m and axial force of 200 N. We recorded and analyzed the following: (1) stiffness of the two fixation systems, (2) hardware stress in the two fixation systems, and (3) stress on the endplate adjacent to the 3D-printed prosthesis. Results The fixation strength of Model B was enhanced by the screws in the artificial pedicle, which was mainly manifested as an improvement in rotational stability. The stress transmission of the artificial pedicle fixation screws reduced the stress on the posterior rods and endplate adjacent to the 3D-printed prosthesis in all directions of motion, especially in rotation. Conclusions After TES, the posterior long-segment fixation combined with the anterior 3D printed prosthesis could maintain postoperative spinal stability, but adding artificial pedicle fixation increased the stability of the fixation system and reduced the risk of prosthesis subsidence and instrumentation failure.